Atherogenic effect of systemic lupus erythematosus pts blood serum - Z S Alekberova; E V Gerasimova; I A Sobenin (Научно-практическая ревматология)
Objective. To study relation of SLE pts blood serum atherogenicity to disease activity and corticosteroids (CS) administration. Methods. 40 young women with SLE were included. 20 of them did not received CS (group 1) and 20 were treated with small doses of CS (<15 mg/day) for a long time (group 2). Duration of the disease was longer in group 2 and SLEDAI indexes were higher in group 1. Control group consisted of 20 healthy women. Serum atherogenicity was examined in BALB/c mice peritoneal macrophages culture by accumulation of intracellular cholesterol (CH) induced by pts blood serum. Results. Most of pts blood serum (90%) and only 15% control blood serum possessed atherogenic potential causing 2-fold rise of intracellular cholesterol level. Frequency of serum atherogenic activity in pts having SLE for a long time was higher. Serum atherogenic activity in group 1 was higher than in group 2 (221±13% and 185±11 % respectively, p=0,044). Atherogenicity correlated with SLEDAI index (r=0,82, p=0,04). No correlation was found between atherogenicity and lipid fractions. Conclusion. Serum atherogenecity is directly dependent on disease activity what shows the significance of immunological changes in atherogenesis in SLE pts